Pengertian Seni sebagai Pengantar Kuliah Sejarah Seni Rupa - John Felix (Humaniora, 2012)
Until these days, for most people art is something that is abstract, hard to understand, and beyond their capability to understand. Every people asked about art will have their own opinion or definition about art, and these definitions are various to each other. For the student who is in the middle of class or course especialy the one that is related to art, the unpleasent impact of not knowing what is the meaning of art will be experienced in every class, especially in the History of Western Art, History of Indonesian Art or History of Graphic Design. Students who don’t understand the meaning of art will have difficult time to absorb what exactly the purpose of art is, why human made art, which item is art and which item is not art. This writing tries to explain the definition of art from several diffrent angles of view. The goal of the writing is to make the students who are in the middle of learning anything relating to art, first have an understanding about what art is. For the lecturer, this writing will give them something to make their work easy on lecturing about anything relating to art because the student has already understood about what art is.